The Sources of Moisture in the Sand Dunes – The Example of the Western Sahara Dune Field - Żmudzka, Elwira; Woronko, Dariusz; Dłużewski, Maciej (Quaestiones Geographicae, 2014)
Climatic and meteorological conditions may limit the aeolian transport within barchans. An explanation of that issue was the main goal of the investigation held in Western Sahara dune fields located around Tarfaya and Laâyoune. Particular attention was paid to the factors causing the moisture content rising of the sand dune surface layer, which could influence the wind threshold shear velocity in the aeolian transport. The wetted surface layer of sand, when receiving moisture from precipitation or suspensions, reduces the aeolian transport, even in case of wind velocity above 4-5 m s-1. Fog and dew condensation does not affect the moisture of deeper sand layers, what occurs after rainfall.